Study and Application of Slon Magnetic Separator in the Purification of Non-metallic Ores - Z. Q. He (International Mineral Processing Congress, 2014)
This paper introduces the structure and working principle of SLon magnetic separator that has excellent performance in iron removal, and summarizes a part of the examples of applications, which applies this machine to remove iron from non-metallic ores, and shows widespread prospect of application of this machine in the purification of non-metallic ores.